WORKING FOR EUROPE? SOCIALIZATION IN THE EUROPEAN COMMISSION AND AGENCIES OF THE EUROPEAN UNION. (18th April 2013) - SUVARIEROL, SEMIN; BUSUIOC, MADALINA; GROENLEER, MARTIJN
<x xml:space="preserve">Abstract</x> The trend towards flexible career arrangements has not left EU institutions untouched, as is manifest in the growing reliance on temporary and part‐time officials. How does the increasing career hybridity within and across EU institutions affect European socialization, i.e. the extent to which officials embody the spirit of 'working for Europe' and adopt supranational norms? We conceptualize European socialization as a mutually reinforcing process shaped by the interaction of officials with the institutions of which they are members. We argue that a focus on career arrangements provides a good starting point as these arrangements shape individuals' interaction with the organization. Consequently, they generate diverging socialization processes which lead to different socialization products. Our empirical insights are based on a study of different types of career arrangements within the European Commission bureaucracy and specialized and independent EU agencies through structured and semi‐structured interviews and surveys with officials.